The impact of the gut microbiota on the reproductive and metabolic endocrine system - Qi, Xinyu; Yun, Chuyu; Pang, Yanli; Qiao, Jie (Gut microbes, 2021)
As the gut microbiota exerts various effects on the intestinal milieu which influences distant organs and pathways, it is considered to be a full-fledged endocrine organ. The microbiota plays a major role in the reproductive endocrine system throughout a woman's lifetime by interacting with estrogen, androgens, insulin, and other hormones. Imbalance of the gut microbiota composition can lead to several diseases and conditions, such as pregnancy complications, adverse pregnancy outcomes, polycystic ovary syndrome (PCOS), endometriosis, and cancer; however, research on the mechanisms is limited. More effort should be concentrated on exploring the potential causes and underlying the mechanisms of microbiota-hormone-mediated disease, and providing novel therapeutic and preventive strategies.As the gut microbiota exerts various effects on the intestinal milieu which influences distant organs and pathways, it is considered to be a full-fledged endocrine organ. The microbiota plays a major role in the reproductive endocrine system throughout a woman's lifetime by interacting with estrogen, androgens, insulin, and other hormones. Imbalance of the gut microbiota composition can lead to several diseases and conditions, such as pregnancy complications, adverse pregnancy outcomes, polycystic ovary syndrome (PCOS), endometriosis, and cancer; however, research on the mechanisms is limited. More effort should be concentrated on exploring the potential causes and underlying the mechanisms of microbiota-hormone-mediated disease, and providing novel therapeutic and preventive strategies.